OPTIMALISASI PEMANFAATAN ENERGI LISTRIK TENAGA SURYA SKALA RUMAH TANGGA - Dafi Dzulfikar; Wisnu Broto (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Indonesia as a country has various types of energy resources a sufficient number of abundance. Location of Indonesia is in the Khatulistiwa region, those regions Indonesia would always be sunlit for 10 until 12 hour a day. Indonesia as a tropic country has development potential and energy utilization as one of many solar energy conversion systems, this solar energy conversion systems can be applied to resolve the depletion fuel reserves existing conventional. Data Directorate General of Electricity and Energy Development in 1997. Electricity installed capacity solar power in Indonesia reached 0,88 MW of the available potential 1.2 x 109 MW. Types of Monocristalline solar cell is the most efficient panels, generate electric power per unit area of the highest. Have efficiences up to 15%. The downside of this type of panel is will not work either in the light of the sun is less (shady), efficiency will drop dramatically in cloudy weather. Photovoltaic cell always covered by a cover which is derived from a glass. Like other glass items, then the optical output from photovoltaic cell also heavily influenced by the orientation to the sun due to variations in the angle of reflection glass. Keywords : optimization, Solar cell, household.